Pergantian Antar Waktu Anggota Saniri Negeri Tanpa Usulan Soa Dan Badan Saniri Negeri - Rikumahu, Valentino Victor Exel; Salmon, Hendrik; Mustamu, Julista (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2023)
This research was motivated by Central Maluku Regency Regional Regulation Number 04 of 2006 concerning Guidelines for Structuring State Saniri or State Consultative Body. This regulation mandates that members of Saniri Negeri are representatives of genealogical elements of society, in this case Soa, so that Soa has the authority to send representatives as members of Saniri Negeri. This type of research is normative legal research, the problem approach in this research is the statutory approach, and the case conceptual approach, the sources of legal materials are primary legal materials and secondary legal materials, legal materials that have been collected and grouped using a statutory approach, then synchronized with the legal concepts and principles studied to be analyzed normatively to answer the legal issues studied based on the approach used in this research. The results of this research are that the Regent's decision to make interim changes to the members of Saniri Negeri without a proposal from Soa and Saniri Negeri is a decision that does not meet the requirements for the validity of a decision, namely authority, procedure and substance which results in the decision being invalid or can be cancelled.